Combination of deferiprone and Phaleria macrocarpa L. ethanolic fruit extract prevents cardiomyopathy in a hemosiderosis rat model - Andi Gunawan, Ari Estuningtyas, Agian Jeffilano Barinda, Hans Joachim Freisleben (Journal of Applied Pharmaceutical Science, 2025)
Hemosiderosis refers to the deposition of surplus iron in body tissues without evidence of structural damage. This condition predominantly afflicts patients with thalassemia who receive recurrent blood transfusions. Iron overload (IO) provokes the elevation of nontransferrin-bound iron (NTBI) and the generation of reactive oxygen species, ultimately culminating in cardiomyopathy. Deferiprone (DFP), a conventional iron-chelating agent, exhibits a range of side effects, including agranulocytosis. Phaleria macrocarpa, commonly known as Mahkota Dewa, contains mangiferin, a polyphenolic xanthone glucoside with iron-chelating properties. The combination of P. macrocarpa fruit extract and DFP is anticipated to reduce side effects and avert the onset of cardiomyopathy. This study employed 36 male Sprague Dawley rats subjected to both P. macrocarpa fruit extract and DFP, while simultaneously inducing IO during the course of treatment. The measured parameters encompassed cardiac iron levels, myocardial malondialdehyde (MDA) levels, plasma levels of brain natriuretic peptide (BNP), and the activation of senescence genes p21 and SUR2A. The combined administration of P. macrocarpa extract and a half-dose of deferiprone (DPM2) substantially lowered cardiac iron levels, myocardial MDA content, and plasma BNP levels. Notably, the expression of senescence genes p21 and SUR2A, regarded as pivotal indicators of cardiomyopathy, was universally suppressed across all treatment groups.
Keywords: Hemosiderosis, Phaleria macrocarpa fruit extract, deferiprone, cardiomyopathy